Biorremediación de suelos contaminados con hidrocarburos a través de microorganismos nativos a nivel de laboratorio, periodo 2023. - Donoso Cáceres, Dennis Steven (2023)
This research was directed to the microorganisms analysis present in the soils, what have suffered oil spills near the production stations vicinity from Petroecuador Ep, located in the Dayuma parish, Orellana province in the Auca oil field with the aim by assessing the soils remediation capacity of said unicellular organisms, which have been exposed to hydrocarbons, due to operational accidents in the area; the purpose this study was to verify the carbide resistant microbiota presence and performance, looking at its remediation performance with natural attenuation stimuli, such as; redox methods and glucosa addition to compare the microorganisms potential their contaminants removal in the soil. It was carried out cultivable microorganisms isolation techniques, through specific culture media use after making serial dilutions up 10−5 . Subsequently, they were classified the associated microbial groups, through different methods, such as morphological, Gram staining and biochemical tests, the purpose was to identify the microorganisms bacterial genus. Further, it was implemented a randomized block design (DBA) with three treatments TO (Soil + Hydrocarbon + water), T1 (Soil + hydrocarbon + water + aeration) and T2 (soil + hydrocarbon + water + molasses). In the results statistical analysis, it was used an ANOVA with a 5% Tukey test. Getting as results, the bacteria presence belonging to the Enterobacteriaceae family, by being the predominant genus Serratia Sp with a 39% percentage. Other identified genera included Shigella Sp at 17%, Hafnia Sp at 11%, Yersina Sp at 11%, Enterocolitica Sp at 6%, Citrobacter Sp Freundi Sp at 6%, Proteus Sp at 6%, Klebsiella Sp with 6% and Enterobacter Sp with 6%. Finally, it was observed, which applied two from three treatments achieved to degrade the hydrocarbons present in the contaminated soil, with the T3 treatment being the most effective with a total hydrocarbons (TPHs) 7484 mg/kg degradation rate. Concluding that, if there are micrograms capable by resisting the hydrocarbons effects present in the soil from Dayuma parish, they also are capable by degrading 77% in soils contaminated by hydrocarbons.